Relation between probiotic milk administration and some bone turnover markers - Chaila, Zulema (2005)
The evaluation of several biochemical markers can reflect the overall skeletal rate of bone turnover. Scarce information about the effects of probiotic foods on the calcium metabolism and bone turnover markers is available. A fermented milk containing probiotic lactobacilli, as a natural strategy to prevent or slow the bone loss process in perimenospausal women, was assayed. A randomized double-blind study with apparently healthy adult women was undertaken to assess whether an improvement of markers of bone turnover levels can be achieved after oral administration of lactobacilli. The results obtained from urinary Deoxypyridinoline levels on day 0 and day 35 indicated significant differences (p<0.05) between perimenopausal women receiving probiotic and those receiving placebo. The urinary type I collagen cross-linked N-telopeptide, did not showed significant differences (p<0.05) between day 0 and day 35 of women included in Test group. In each woman of Control group the relation calcium/creatinine did not show significant differences (p>0.05) between day 0 and day 35. The results obtained from two bone formation markers, serum osteocalcin and bone-specific alkaline phosphatase did not show significant differences (p>0.05). The results obtained in the present work could infer that the fermented milk consumption decreased the calcium loss in adult women.